Principal Functions of Nonselfadjoint Discrete Dirac Equations with Spectral Parameter in Boundary Conditions. (21st October 2012) - Aygar, Yelda; Olgun, Murat; Koprubasi, Turhan
Abstract : Let L denote the operator generated in ℓ 2 ( ℕ, ℂ 2 ) by a n + 1 y n + 1 ( 2 ) + b n y n ( 2 ) + p n y n ( 1 ) = λ y n ( 1 ), a n - 1 y n - 1 ( 1 ) + b n y n ( 1 ) + q n y n ( 2 ) = λ y n ( 2 ), n ∈ ℕ, and the boundary condition ( γ 0 + γ 1 λ ) y 1 ( 2 ) + ( β 0 + β 1 λ ) y 0 ( 1 ) = 0, where ( a n ), ( b n ), ( p n ), and ( q n ), n ∈ ℕ are complex sequences, γ i, β i ∈ ℂ, i = 0, 1, and λ is an eigenparameter. In this paper we investigated the principal functions corresponding to the eigenvalues and the spectral singularities of L .